Pelagic seabirds in coastal waters of the Western Ligurian Sea: occurrence and seasonality (Avocetta, 2025)
Seabirds are an heterogeneous group of birds that, due to their behaviour and at-sea distribution, remain difficult to study when compared to other species. In the Liguro-Provençal basin (Mediterranean Sea), the fragmentary information of presence and number of individuals available fails to capture the variability of occurrence of these species year-round and at smaller regional scales. This study aimed to fill these gaps in seabirds’ presence and phenology for the coastal Western Ligurian Sea. Data were collected opportunistically at sea, year-round, from June 2018 to May 2022. 274 surveys were conducted, totalling 1,522.91 hours of search time year-round: 12 species of seabirds, excluding seagulls, cormorants, shags, and landbirds, were identified. Observations of species and group size were collected to estimate cumulative seasonal encounter rates (ER) for all species and seasonal ERs for the most common taxa. Spring and autumn had the highest ER cumulative for all species, as these are migratory periods for multiple species. These are also periods of the highest presence of the most sighted species - Yelkouan Puffinus yelkouan and Scopoli’s Shearwaters Calonectris diomedea - at French breeding colonies. Species also observed in large numbers were the Northern Gannet Morus bassanus and the Sandwich Tern Thalasseus sandvicensis, whose sightings matched their migratory phenology. Other northern breeding species, such as Atlantic Puffin Fratercula arctica, and more rare species like skua spp. were also recorded. The presence of migratory species year-round indicates the region is an important non-breeding and foraging ground for individuals not taking part in the pre-breeding migrations and for shearwaters breeding in the Tyrrhenian Sea. This study highlights the importance of the Western Ligurian Sea for pelagic seabird species, emphasizing the need for targeted conservation actions to enhance their protection.
Keywords: Seabirds; Mediterranean; Coastal; Shearwater; Gannets